TINJAUAN SISTEMATIS KARAKTER TOLERANSI DALAM PEMBELAJARAN FISIKA - Avila, Flor Amara; Salsabilah, Wanada Siti; Triani, Elza (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This research is the first to conduct a systematic review of the concept of tolerance character in the context of physics learning. The research aims to explore the definition, measurement, and development of tolerance character among high school students through physics learning. The method used in this research is the literature review method. Sampling in this study was carried out by looking for several scientific articles from previous research on the character of tolerance found on Google Scholar, which were then examined and conclusions drawn. Results of the analysis of articles regarding the character of tolerance in learning physics in high school found that the character of tolerance is a character that needs to be instilled in students at the high school education level through learning physics. The research also identified the benefits, challenges, and strategies of fostering tolerance in physics learning, such as enhancing students’ critical thinking, communication, and collaboration skills, overcoming misconceptions and stereotypes, and using inquiry-based, problem-based, and cooperative learning methods. This character of tolerance can be taught and applied in education through learning, one of which is learning physics. The novelty of this research is that it provides a comprehensive and systematic overview of the existing literature on the concept of tolerance character in the context of physics learning. The research also contributes to the literature on physics education and character education by highlighting the role of physics learning in enhancing the tolerance character of high school students.